Colloidal stable silica encapsulated nano-magnetic composite as a novel bio-catalyst carrier - Gao, X; Yu, K; Tam, K; Tsang, S (2003)
A colloidal stable silica-encapsulated magnetic nano-composite of a controlled dimension is, for the first time, employed to carry β-lactamase via chemical linkage on the silica overlayer: activity study reflects that this new type of immobilisation allows site (enzyme) isolation, accessibility as good as free enzyme and recovery and reusability upon application of magnetic separation.